A consensus conference report on defining the eligibility criteria for pediatric palliative care in Italy - Momcilo Jankovic; Lucia De Zen; Federico Pellegatta; Pierina Lazzarin; Marina Bertolotti; Luca Manfredini; Antonino Aprea; Luigi Memo; Antonio Del Vecchio; Rino Agostiniani; Franca Benini (BMC, 2019)
Abstract Background The definition of the eligibility criteria of newborn, infant, child, or adolescent patients for palliative care (PC) is complicated by the fact that these patients generally present with very specific case histories that make it inadvisable to directly adopt existing PC protocols devised for adult patients. Thus, the goal of this paper is to define a standard set of criteria for establishing pediatric palliative care (PPC) eligibility. Methods The method adopted was that of the consensus conference. According to the guidelines issued by the Higher Institute of Health, the Board of the Italian Society for Palliative Care (i.e. steering committee) appointed a multidisciplinary group of eight health care professionals (i.e. doctors, nurses and psychologists) who worked from May 2014 to February 2016 to reach a consensus over PPC eligibility. This panel of relevant experts redacted a report summarizing all available scientific information concerning PPC, which was then submitted to the attention of a multidisciplinary jury composed of specialists and non-specialists of the field. The document thus produced was subsequently reviewed by an extended team of experts. Results The consensus conference drafted a final document determining the guidelines for PPC eligibility of newborns, infants, children, and adolescents suffering from either oncological or non-oncological diseases. Conclusions This report provides health care providers with practical guidelines on how to define the eligibility of pediatric patients for PPC. Given the current situation in Italy, these guidelines will be instrumental in assisting the implementation of adequate generalist and specialist PPC services as well as in helping policymakers draft and implement national legislation pertaining to PPC.